Saving Other Children from Other Women: Born Into Brothels - Duncan, Patti (Journal of the Motherhood Initiative for Research and Community Involvement, 2013)
In this paper the author explores representations of rescue and motherhood in the 2005 film, Born Into Brothels, which won the Academy Award for Best Feature Documentary. Embedded in a colonial history of looking relations, the film embodies white Euro-American fantasies about children in “other” parts of the world. In the film, Indian children are portrayed as innocent, vulnerable, preyed upon for prostitution, and in need of rescue. Indian women, on the other hand—their mothers—are portrayed as impoverished, incompetent, and eager to prostitute their own children. Through its decontextualized portrayal of the sex industry in Calcutta and its cinematic erasure of local efforts to improve the lives of sex workers and their children, Born Into Brothels tells a familiar story that appeals to western notions of rescue. The author asks: Why are the children worth saving, but their mothers are not? And, how are contemporary practices of sex work in Calcutta structured by the postcolonial state and its relationship to other social, political, and economic contexts?